2022
DOI: 10.3389/fmolb.2022.937979
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Necroptosis-Associated Long Non-Coding RNA Signature to Predict Prognosis and Immune Response in Hepatocellular Carcinoma

Abstract: Background: Necroptosis is a form of programmed cell death, and studies have shown that long non-coding RNA molecules (lncRNAs) can regulate the process of necroptosis in various cancers. We sought to screen lncRNAs associated with necroptosis to predict prognosis and tumor immune infiltration status in patients with hepatocellular carcinoma (HCC).Methods: Transcriptomic data from HCC tumor samples and normal tissues were extracted from The Cancer Genome Atlas database. Necroptosis-associated lncRNAs were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Of the seven CRLs in our study, MIR9-3HG, POLH-AS1, and WDFY3-AS2 are reported to play important roles in various cancers by regulating ferroptosis [ 31 33 ]. Additionally, POLH-AS1 was identified to regulate the process of necroptosis in hepatocellular carcinoma [ 34 ]. It was also reported that MIR9-3HG knockdown inhibited cell proliferation and promoted apoptosis in cervical cancer [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the seven CRLs in our study, MIR9-3HG, POLH-AS1, and WDFY3-AS2 are reported to play important roles in various cancers by regulating ferroptosis [ 31 33 ]. Additionally, POLH-AS1 was identified to regulate the process of necroptosis in hepatocellular carcinoma [ 34 ]. It was also reported that MIR9-3HG knockdown inhibited cell proliferation and promoted apoptosis in cervical cancer [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…And functional studies indicated that LINC00942 confers chemoresistance to GC cells by impairing apoptosis and inducing stemness (14). Previous researches have proven that AC131009.1 and were associated with necroptosis, suggesting that they play roles in different ways of programmed cell death (15). AC090772.3 was found to be highly expressed in the HCC as a ceRNA related to hypoxia(16) and more in-depth research about AC090772.3 is needed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…AL031985.3 is associated with liver cancer ferroptosis, cuproptosis, pyroptosis, and autophagy-related prognosis models[28-30], while AC026412.3 is included in the model predicting copper mortality and focal mortality in hepatocellular carcinoma [31,32]. MKLN1-AS and TMCC1-AS1 are also part of liver cancer-related models such as pyroptosis, ferroptosis, autophagy, necroptosis, and autophagy, respectively [29,31,[33][34][35]. Collectively, the identi ed lncRNAs may be closely related to liver cancer apoptosis and may offer new avenues for targeted therapy.…”
Section: Discussionmentioning
confidence: 99%